In Silico Analysis of Kaempferol from Foeniculum vulgare and Coumarin from Alyxia reinwardtii Targeting Anti-Apoptotic Proteins: Potential Anticancer Agents - Pinanti, Honesty Nurizza; Mubarakati, Nurul jadid (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2025)
Foeniculum vulgare and Alyxia reinwardtii are two herbal plants frequently co-utilized by Javanese people in Indonesia to treat various diseases, as evidenced by ancient manuscripts about traditional medicine (Jamu). However, the potential of the combination of kaempferol and coumarin, the major bioactive compounds derived from each plant, to inhibit BCL-2 and BCL-XL anti-apoptotic proteins in cancer has not yet been investigated. Therefore, this study aimed to identify the inhibitory activity of kaempferol, coumarin, and their combinations on BCL-2 and BCL-XL through in silico studies. The physicochemical properties of both compounds were predicted using the SwissADME web server. Meanwhile, the docking activity prediction of these compounds on BCL-2 and BCL-XL was performed using the molecular docking method with HEX 8.0.0 CUDA. Docking visualization was performed using BIOVIA Discovery Studio 2020 Client. The results of this study indicated that kaempferol could bind the binding groove of both BCL-2 (-246.40 kcal/mol) and BCL-XL (-245.76 kcal/mol), whereas coumarin only interacted with the binding groove of BCL-XL (-160.61 kcal/mol). The combination of the two compounds exhibited a stronger interaction with BCL-2 (-248.50 kcal/mol) and BCL-XL (-260.43 kcal/mol) compared to each compound individually. Therefore, the combination of these compounds is predicted to exhibit greater anticancer potential than either kaempferol or coumarin alone. Nevertheless, further extensive studies are required to validate the findings of this study.